Nasal polyposis: a semiquantitative morphometric histopathological study - Trivić, Aleksandar; Tomanović, Nada; Krejović Trivic, Sanja; Milovanović, Jovica; Boričić, Ivan; Jotić, Ana; Folić, Miljan; Ćolović Čalovski, Ivana; Miković, Nikola; Tatić, Zoran (Vojnosanitetski pregled, 2021)
Background/Aim. Nasal polyps are inflammatory hypertrophic proliferations of the sinonasal mucosa composed of both epithelial and stromal elements. The aim of this study was to determine histopathological hallmarks of nasal polyposis via semiquantitative morphometric study. Methods. The study comprised 77 patients with chronic rhinosinusitis and nasal polyposis (CRSwNP) that underwent functional endoscopic sinonasal surgery performed by the same surgeon. The control group consisted of 9 different nasal mucosal samples that were taken from patients without CRSwNP that underwent functional and esthetic surgery. Morphometric analysis included gradation of tissue edema within polyps, thickening of epithelial basal membrane, degree of inflammation, presence/absence of metaplasia within epithelium, degree of fibrosis within polyps, and percentage of inflammatory cells within inflammatory infiltrate (lymphocytes, macrophages, plasma cells, neutrophils and eosinophils). Results. As expected, samples from the study group showed significantly higher degree of inflammation than samples from the control group (χ2 = 35.89, with p < 0.01). Degree of fibrosis in nasal polyposis was in positive correlation with duration of symptoms (r = 0.25, p < 0.05) and with percentage of macrophages in inflammatory infiltrate (r = 0.26, p < 0.05). Patients with nasal polyposis had significantly lower number of lymphocytes (r = -7.66, p < 0.01), but significantly higher number of eosinophils (r = 3.84, p < 0.01), macrophages (r = 3.34, p < 0.01) and plasma cells (r = 3.14, p < 0.01) than controls (p < 0.01). Conclusion. Tissue samples from patients with nasal polyposis show significant changes that reflect in various degrees of inflammation, fibrosis and basement membrane thickening which may contribute to more difficult surgical management and perioperative complications such as bleeding.
Keywords: nasal polyps; otorhinolaryngologic surgical procedures; postoperative complications; histology